Intervensi untuk Meningkatkan Regulasi Emosi pada Individu dengan Disabilitas Intelektual: Literature Review - Hilmi Dzaki; Annisa Rahmah Ghaffari; Eni Novita Sari Febriani; Nesya Nabilfaizy Albib; Iftita Rahmi (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Individuals with intellectual disabilities may experience difficulties in recognizing emotions, understanding the cause-and-effect relationship of emotions, as well as problems with self-control, impulse inhibition, and emotional regulation. Emotional regulation is therefore an essential aspect in addressing issues related to managing emotions. Given the important role of emotional regulation for individuals with intellectual disabilities, there is a need for systematic intervention efforts, starting with an initial assesment. This study aims to identify interventions that can improve emotional regulation in individuals with intellectual disabilities. The study was conducted using a descriptive literature review. The inclusion criteria for the literature search were: (1) articles based on primary research, (2) focusing on emotional behavior or challenging behavior in individuals with intellectual disabilities, (3) full-text access available, and (4) published within the last 10 years (5) journals indexed from Sinta 5 up to Scopus. The results of this review indicate that several interventions are effective in enhancing emotional regulation in individuals with intellectual disabilities. These include Differential Reinforcement of Alternative Behavior, Cognitive Behavioral Therapy (CBT), a combination of CBT and behavior-analytic approaches, psychomotor interventions, Leadership for Empowerment and Abuse Prevention (LEAP), assertive training, and Soles of the Feet meditation (UK SoF). Abstrak. Individu dengan disabilitas intelektual mungkin mengalami kesulitan untuk dapat mengenali emosi, memahami sebab-akibat dari emosi, serta memiliki masalah untuk mengendalikan diri, menahan dorongan diri, serta mengelola emosi. Regulasi emosi menjadi suatu hal yang penting dalam membantu masalah terkait pengelolaan emosi. Melihat pentingnya peran regulasi emosi bagi individu dengan disabilitas intelektual, maka dibutuhkan sejumlah upaya berupa intervensi yang sistematis seperti yaitu asesmen awal. Penelitian ini bertujuan untuk dapat mengetahui terkait intervensi apa saja yang mampu meningkatkan regulasi emosi pada individu dengan disabilitas intelektual. Penelitian ini disusun menggunakan kajian literatur deskriptif. Kriteria inklusi dalam pencarian literatur yang digunakan yaitu 1) artikel berasal dari penelitian empris 2) berfokus terhadap perilaku emosional atau perilaku menantang individu dengan disabilitas intelektual 3) dapat diakses full text 4) terbit dalam 10 tahun terakhir 5) jurnal terindeks Sinta 5 hingga Scopus. Hasil dari penelitian ini menunjukkan bahwa terdapat sejumlah intervensi yang efektif dalam meningkatkan regulasi emosi pada individu dengan disabilitas intelektual diantaranya meliputi intervensi differential reinforcement of alternative behavior, Cognitive Behavioral Therapy (CBT), perpaduan pendekatan CBT dengan analisis perilaku (behavior-analytic), psikomotorik (psychomotor), Leadership for Empowerment and Abuse Prevention (LEAP), pelatihan asertif (assertive training), serta meditasi Soles of The Feet (UK SoF).